Sex Differences in Antisocial Personality Disorder: Results From the National Epidemiological Survey on Alcohol and Related Conditions - Alegria, Analucia A. (2013)
Despite the 3:1 prevalence ratio of men versus women with Antisocial Personality Disorder (ASPD), research on sex differences on correlates of ASPD in the general population is scarce. The purpose of this study was to examine sex differences in childhood and adult adverse events, lifetime psychiatric comorbidity, and clinical correlates of DSM–IV ASPD. The sample included 819 men and 407 women with DSM-IV ASPD diagnosis. Data were derived from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) (N = 43,093). Compared to men, women with ASPD reported more frequent childhood emotional neglect (AOR = 2.25; 95% CI: 1.52–3.34) and sexual abuse (AOR = 4.20; 95% CI: 2.78–6.35), any parent-related adverse event during childhood (e.g., parental substance use disorder) (AOR = 2.47; 95% CI: 1.60–3.82), and adverse events during adulthood (AOR = 4.20; 95% CI: 2.78–6.35). Although women with ASPD present less violent antisocial behaviors and higher rates of aggressiveness and irritability (OR = 0.46; 95% CI: 0.31–0.67), they have higher rates of victimization, greater impairment, and lower social support. Our findings suggest increased mental health needs in women with ASPD, meriting development of different treatment programs for women and men.